Unemployment rate predicts anger in popular music lyrics: evidence from top 10 songs in the United States and Germany from 1980 to 2017 - Qiu. Lin (2022)
Popular music has been shown to reflect cultural characteristics and psychological change in a society. However, little is known about how popular songs are related to the socioeconomic conditions. In this research, we analyzed the annual top 10 songs from United States and Germany between 1980 and 2017, and found that the unemployment rate predicted the amount of anger but not anxiety or sadness in lyrics in both countries. Our research contributes to the literature on popular media culture by revealing that top song lyrics may reflect public sentiment toward the socioeconomic environment. It highlights the possibility of using top song lyrics as an alternative measure of public sentiments. (PsycInfo Database Record (c) 2021 APA, all rights reserved)